2014
DOI: 10.1111/jocn.12639
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the quality of Emergency Nurse Practitioner services for patients presenting with minor injuries to one rural urgent care centre in the UK: a descriptive study

Abstract: This study provides some evidence to support the continued expansion of the emergency nurse practitioner service in rural settings in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
1
13
0
1
Order By: Relevance
“…). Also other models, like emergency nurse practitioner service for patients with minor injuries, are implemented and although promising rarely evaluated (McDevitt & Melby ). These developments fuel the need for more evaluation of NPs offering out‐of‐hours care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Also other models, like emergency nurse practitioner service for patients with minor injuries, are implemented and although promising rarely evaluated (McDevitt & Melby ). These developments fuel the need for more evaluation of NPs offering out‐of‐hours care.…”
Section: Discussionmentioning
confidence: 99%
“…). In addition, research in emergency care shows that NPs provide a valuable, safe and effective service (McDevitt & Melby , McDonnell et al . , Pirret et al .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the literature demonstrating that patients were very satisfied with NP health care services. [15,16,21,22,30,32,[34][35][36] Furthermore over 98% of participants would seek the services of a NP in the future. The findings also indicate that rapport building, accessibility, flexibility with scheduling and consistency of health care provider, contributed to patient satisfaction which corresponds with research findings.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship with the primary health provider was reported as having the greatest significance to patient satisfaction with respect and trust reported as significant factors. [10][11][12] Several studies in Australia, United Kingdom, United States and Canada [13][14][15][16][17][18][19] reported that patients are satisfied with the care received from NPs. The authors cite satisfaction related to NP communication increased especially when education was provided on disease prevention, health promotion and chronic disease management.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…w USA, Kanadzie, Australii, Wielkiej Brytanii, Irlandii, Południowej Afryce [18,20,21]. Pracę pielęgniarek w tych punktach opieki cechuje bezpieczeństwo, efektywność i wysoki poziom satysfakcji pacjenta, a głównymi jej wyznacznikami są: uzyskiwanie wyczerpujących informacji na temat urazu, krótki czas oczekiwania, dogodność dostępu do usług [21,22]. Równo-cześnie wykazano wysoką dokładność diagnostyczną pielę-gniarek ratunkowych oraz prawidłowość zastosowanego leczenia [23,24].…”
Section: Analizy Statystyczneunclassified